NEOLOGISMS IN THE MODERN ITALIAN LANGUAGE - Lakhtionova , Kateryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article considers and analyzes the appearance of modern neologisms in the Italian language, the first references to the fixation of such neologisms, their use in the scientific and linguistic environment (modern lexicology). The structure of recorded new words is studied using the most common prefixes of Latin and Greek origin, nouns, adjectives and adverbs. The analysis of such vocabulary aims to explain their meaning and excludes words such as snobbery, linguistic doublets, slang and vulgarisms.Italian language, as any other language has its mechanisms of word formation and composition related to the enrichment of the vocabulary and the resolution of its lexical problems. It is not easy for Italian language to administer these mechanisms, its structures and microstructures of word formation. It is in a situation which it has to deal with the systems of word formation, which come from Latin, and also that derives from and functions from the nature of Italian. The systems of word-formation, which come from Latin, can be called to be in a “numb” situation, but also in a state that can be used dynamically in Italian language. The phenomenon of word formation stats as a morphological one, but certainly it develops and interferes as a lexical-semantic phenomenon, too. Neologisms in Italian, as in other languages, come from other foreign languages that are called “borrowed words”. Italian language, concerning neologisms, that derive other languages, has a special “attitude”, compared to other European languages. Some European languages have a more refraction attitude in relation to neologisms and their reaction is very interfering and modifying, even alternating. Whereas, concerning Italian, there is a specific reaction, which comes from the phonetic aspect. Surprisingly, phonetics seems to have a very affective role in lexicology and semantics of a language, in our case of Italian, but that does not result like this.The author's personal contribution consists in the study and systematization of modern Italian neologisms, which are recorded in modern basic dictionaries.__________References:• Cortelazzo, M., Cardinale, U. Dizionario di parole nuove 1964-1984 (Loesher Editore, Torino, 1986), 209.• Granzotto, P. Breve storia delle parole. Repertorio dei dubbi linguistici e degli errori comuni (Casa editrice di lettere Firenze, 1998), 69.• Dizionario delle parole difficile Tascabili Economici (Newton, Roma, 1994), 93.
Keywords: neologisms, lexical base of the modern Italian language, dialectisms, fixation of neologisms, linguistic aspect of language evolution, language register, snobbery, linguistic doublets, vulgarisms